Fostering student entrepreneurship through a holistic ecosystem approach in higher education - Mahfud, Imam (Privietlab, 2025)
Entrepreneurship has emerged as a strategic instrument for economic development and employment generation, particularly among youth in developing countries, such as Indonesia. In the context of higher education, university students represent a promising demographic with digital literacy, academic knowledge, and broad social networks. However, their entrepreneurial potential remains underutilized because of various structural and individual-level challenges, including limited business management skills, inadequate institutional support, and insufficient access to capital. This study explores multidimensional strategies to cultivate entrepreneurship among university students by analyzing the roles of higher education institutions, digital technology adoption, financial support mechanisms, and cross-sector collaboration. Using a qualitative descriptive methodology, this research draws upon secondary data comprising policy documents, academic literature, university program reports, and case studies. Thematic analysis reveals four strategic pillars: the integration of entrepreneurship education into formal curricula; utilization of digital platforms for business growth; enhancement of student access to financial capital; and the formation of collaborative ecosystems involving universities, industry, and government. The study underscores the importance of embedding entrepreneurship as a core academic and institutional priority and proposes a holistic model to transform students into job creators. These findings provide practical insights for policymakers, educators, and private sector actors aiming to accelerate youth-led entrepreneurship in Indonesia’s higher-education landscape.